EXPLORATION OF STUDENTS' SPEAKING ANXIETY REGARDING FOREIGN LANGUAGE PARTICIPATION IN THE CLASSROOM - Fadia Nuralika; Kustiwan Syarief; Viviana Lisma Lestari (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
ABSTRACTSpeaking is one of the most crucial skills to cultivate and strengthen communication skills. Speaking proficiency is one of the most difficult components of language learning, particularly for those learning a foreign language. Many language learners have difficulty expressing themselves verbally. They frequently struggle with successfully expressing themselves in a new language. They cease communicating due to psychological hurdles or a lack of acceptable words and expressions. The purpose of this study is to investigate students' worries regarding the types of speaking anxiety experiences they have in the classroom. This research employs descriptive qualitative as a research design. Ten EFL students participated as participants, and the researcher used thematic analysis techniques to analyze the data. The findings of this study reveal that ten EFL students can be said to be anxious about speaking English. Some of them are classified as facilitative anxiety and debilitative anxiety. This study is intended to assist EFL students in considering the speaking demands of their language learners in the context of English language teaching and learning. ABSTRAKBerbicara adalah salah satu keterampilan yang paling penting untuk mengembangkan dan memperkuat kemampuan komunikasi. Kemahiran berbicara adalah salah satu komponen pembelajaran bahasa yang paling sulit, terutama bagi mereka yang belajar bahasa asing. Banyak pelajar bahasa yang mengalami kesulitan dalam mengekspresikan diri mereka secara lisan. Mereka sering kali kesulitan untuk berhasil mengekspresikan diri mereka dalam bahasa baru. Mereka berhenti berkomunikasi karena rintangan psikologis atau kurangnya kata-kata dan ekspresi yang dapat diterima. Tujuan dari penelitian ini adalah untuk menyelidiki kekhawatiran siswa mengenai jenis pengalaman kecemasan berbicara yang mereka alami di kelas. Penelitian ini menggunakan deskriptif kualitatif sebagai desain penelitian. Sepuluh siswa EFL berpartisipasi sebagai partisipan dan peneliti menggunakan teknik analisis tematik untuk menganalisis data. Temuan dari penelitian ini mengungkapkan bahwa sepuluh siswa EFL dapat dikatakan cemas dalam berbicara bahasa Inggris. Beberapa di antaranya diklasifikasikan sebagai kecemasan fasilitatif dan kecemasan debilitatif. Penelitian ini dimaksudkan untuk membantu siswa EFL dalam mempertimbangkan tuntutan berbicara dari pembelajar bahasa mereka dalam konteks pengajaran dan pembelajaran bahasa Inggris.